Moisture-permeable sunscreen layered composite fabric and preparation method thereof

By blending hemp fiber and cotton fiber as the inner layer fabric, and using modified polylactic fiber as the outer layer fabric, combining nitrile rubber, alkenyl modified nano zinc oxide and 2-hydroxy-4-(methacryloyloxy)benzophenone and other materials for graft copolymerization, the problems of poor moisture permeability and poor tensile performance of the sunscreen fabric are solved, and good moisture permeability, sun protection and environmental protection performance of the fabric are achieved.

CN119502471AActive Publication Date: 2025-02-25ANHUI LIANYAO INTELLIGENT MANUFACTURING CLOTHING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411769674.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-25
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

In the prior art, the sunscreen fabrics containing polylactic fibers have poor moisture permeability and tensile performance need to be improved.

Method used

Hemp fiber and cotton fiber are blended as the inner layer fabric, and modified polylactic fiber is used as the outer layer fabric, and composited through knitting process. Graft copolymerization is used for materials such as nitrile rubber, alkenyl modified nano zinc oxide and 2-hydroxy-4-(methacryloyloxy)benzophenone to enhance the moisture permeability and sun protection of the fabric.

Benefits of technology

It achieves good moisture permeability and sun protection performance of the fabric, while improving the tensile performance of polylactic fiber, enhancing the environmental protection and use comfort of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119502471A_ABST
    Figure CN119502471A_ABST
Patent Text Reader

Abstract

The invention relates to the field of layered composite fabrics, in particular to a moisture-permeable sunscreen layered composite fabric and a preparation method thereof. The fabric comprises a two-layer structure of an inner-layer fabric and an outer-layer fabric, the inner-layer fabric is prepared by blending China hemp fibers and cotton fibers and has good moisture permeability, the outer-layer fabric is prepared from polylactic acid, the polylactic acid is subjected to modification treatment, and the moisture permeability of the outer-layer fabric is improved. A toughening component nitrile rubber and sunscreen components nano zinc oxide and 2-hydroxy-4-(methylacryloyloxy) benzophenone are introduced, the polylactic acid fabric has good tensile property due to the addition of the toughening component, and the composite fabric has good sunscreen performance due to the addition of the sunscreen component, so that the harm of ultraviolet rays to human skin can be avoided, and the sunscreen effect is good. And the problem that the polylactic acid fabric is yellowed by illumination can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of layered composite fabrics, and in particular to a moisture-permeable and sun-proof layered composite fabric and a preparation method thereof. Background Art

[0002] Sunscreen fabrics are mostly coated with sunscreen components on the surface of the fabric to reflect or absorb ultraviolet rays to achieve the sunscreen effect. However, the existence of the coating layer easily causes the fabric to have poor moisture permeability. In addition, sunscreen fabrics are mostly made of chemical synthetic fabrics, which have poor degradation performance and cause environmental pollution.

[0003] Chinese patent CN117382267B discloses a cool and breathable fabric for sun-proof clothing. The fabric base fabric includes an inner layer and a surface layer. The inner layer is obtained by blending nylon fiber and antibacterial cool polylactic acid fiber, and the surface layer is obtained by blending polyester fiber and antibacterial cool polylactic acid fiber. The base fabric is immersed in a protective liquid to obtain a cool and breathable fabric for sun-proof clothing. However, the immersion treatment easily causes the moisture permeability of the fabric to decrease, and the polylactic acid fiber has the problems of high brittleness and poor tensile properties. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a moisture-permeable sun-proof layered composite fabric to solve the problems in the prior art that the sun-proof fabric containing polylactic acid fibers has poor moisture permeability and needs to improve its tensile properties.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a moisture-permeable sun-proof layered composite fabric comprises the following steps:

[0007] Step 1: adding nitrile rubber, olefin-modified nano zinc oxide and 2-hydroxy-4-(methacryloyloxy)benzophenone into tetrahydrofuran, and mixing by ultrasonication to obtain a monomer dispersion;

[0008] Add dibenzoyl peroxide into chloroform, stir and dissolve to obtain an initiator solution;

[0009] Adding polylactic acid into tetrahydrofuran to dissolve it to obtain a polylactic acid solution, dropping a monomer dispersion and an initiator solution into the polylactic acid solution, reacting after the dropping is complete, settling after the reaction is complete, filtering, washing, and drying to obtain a modified polylactic acid;

[0010] Step 2, melt spinning the modified polylactic acid to obtain polylactic acid fiber filaments;

[0011] The polylactic acid fiber filaments are spun into fabrics through a knitting process to obtain polylactic acid fabrics;

[0012] Step 3: blending hemp fiber and cotton fiber to obtain blended yarn, and spinning the blended yarn into fabric through a knitting process to obtain hemp / cotton blended fabric;

[0013] The hemp / cotton blended fabric is used as the inner fabric and the polylactic acid fabric is used as the outer fabric. The inner fabric and the outer fabric are laminated with equal areas to prepare a moisture-permeable and sun-proof layered composite fabric.

[0014] Preferably, in the step 1, the mass ratio of the polylactic acid solution, the monomer dispersion and the initiator solution is (650-850):(630-870):(52-72); the dropping time of the monomer dispersion and the initiator solution is the same, both are 60-90 min, and the reaction conditions are reflux reaction at a temperature of 60-70° C. for 5-7 h.

[0015] Preferably, in the step 1, in the monomer dispersion, the mass ratio of nitrile rubber, olefin-modified nano zinc oxide, 2-hydroxy-4-(methacryloyloxy)benzophenone and tetrahydrofuran is (60-80):(15-20):(55-70):(500-700).

[0016] Preferably, in step 1: in the initiator solution, the mass ratio of dibenzoyl peroxide to chloroform is 1:(25-35).

[0017] Preferably, in the step 1: in the polylactic acid solution, the mass ratio of polylactic acid to tetrahydrofuran is 100:(550-750).

[0018] Preferably, the alkenyl-modified nano zinc oxide in step 1 is prepared by the following steps:

[0019] The nano zinc oxide is added into an ethanol aqueous solution, and after ultrasonic dispersion, the pH value is adjusted to 3-4 to obtain a nano zinc oxide dispersion liquid. γ-methacryloxypropyltrimethoxysilane is added into the nano zinc oxide dispersion liquid to react. After the reaction is completed, the mixture is filtered, washed, and dried to obtain olefin-modified nano zinc oxide.

[0020] Preferably, the mass ratio of the nano zinc oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 8:(10-15):(100-120), and the reaction conditions are 55-65° C. for 8-10 hours.

[0021] Preferably, in step 2: the melt spinning process includes: a spinning temperature of 220-230°C; a winding speed of 350-450m / min; a drawing temperature of 135-145°C, a drawing ratio of 5 times; and a heat setting temperature of 110-120°C.

[0022] Preferably, in step 2: the fineness of the polylactic acid fiber filament is 1.4-1.6D, and the weight of the polylactic acid fabric is 100-120g / m 2 .

[0023] Preferably, in step 3: the mass ratio of hemp fiber to cotton fiber is (50-60):(40-50), the yarn count of the blended yarn is 40-50S (English count), and the gram weight of the hemp / cotton blended fabric is 100-120g / m 2 .

[0024] Preferably, the blending process comprises: opening the modified spandex fiber and the hemp fiber separately, mixing them, and then sequentially processing them through the steps of mixed opening, carding, drawing, roving and spun spinning.

[0025] Preferably, when the modified spandex fiber and the hemp fiber are opened separately or mixed and opened, the opening process adopts a rotation speed 5-10% lower than that of conventional cotton fiber opening.

[0026] Preferably, the process of the combing step is to use a hairy roller carding machine to comb the mixed fibers, and the rotation speed of the large cylinder of the hairy roller carding machine is 90-100 r / min.

[0027] Preferably, the drawing process adopts a three-pass drawing process, each of which uses 8 strands for feeding, the back zone drafting multiple of the first pass drawing is 1.6-1.8 times, and the back zone drafting multiples of the second and third passes drawing are the same, both 1.05-1.1 times.

[0028] Preferably, the process parameters of the roving process are: the roving Tex twist coefficient is 50-55, and the spindle speed is 460-480r / min.

[0029] Preferably, the process parameters of the spinning process are: the spinning Tex twist coefficient is 340-360, the sliver delivery speed is 12-16 m / min, and the spindle speed is 5000-7000 r / min.

[0030] The invention also discloses a moisture-permeable sun-proof layered composite fabric prepared by adopting the method for preparing the moisture-permeable sun-proof layered composite fabric as described above.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The fabric of the present invention comprises a two-layer structure of an inner fabric and an outer fabric. The inner fabric is made of a blend of hemp fiber and cotton fiber. Both hemp fiber and cotton fiber have excellent moisture absorption performance. The cross section of the hemp fiber presents a hollow structure, and there are many cracks and holes connected to it in the longitudinal direction, so that the hemp fiber has more capillaries, which can quickly diffuse and transfer water to the external environment, thereby achieving good moisture permeability. The raw material for preparing the outer fabric is polylactic acid. As a biodegradable material, polylactic acid is used in combination with hemp fiber and cotton fiber. The fabric has good environmental protection. After being modified, polylactic acid has good sun protection performance. As the outer layer structure of the fabric, the fabric can be made to have the effect of isolating ultraviolet rays.

[0033] The modification of polylactic acid includes grafting toughening component nitrile rubber and sunscreen components nano zinc oxide and 2-hydroxy-4-(methacryloyloxy) benzophenone onto polylactic acid molecules. The introduction of toughening components can effectively overcome the problem of poor tensile properties of polylactic acid due to high brittleness and low elongation at break. The addition of sunscreen components can effectively improve the resistance of polylactic acid fibers to ultraviolet rays, thereby improving the sunscreen properties of polylactic acid fabrics, which can not only avoid ultraviolet damage to human skin, but also improve the problem of yellowing of polylactic acid fabrics themselves due to light exposure.

[0034] Under the action of the initiator, nitrile rubber, olefin-modified nano zinc oxide and 2-hydroxy-4-(methacryloyloxy) benzophenone undergo graft copolymerization on the polylactic acid molecular chain through the carbon-carbon double bonds contained in their respective molecules, and the toughening component and the sunscreen component are chemically bonded to the polylactic acid molecule, thereby avoiding the phenomenon of reduced toughening and sunscreen effect caused by poor dispersion compatibility between the toughening component and the sunscreen component and polylactic acid or migration problems of small molecular organic matter; in addition, nano zinc oxide, as an inorganic filler, can also play a role in strengthening and toughening, and can further improve the tensile properties of polylactic acid fabrics;

[0035] Both the inner fabric and the outer fabric are spun through a knitting process. The fabric has good elasticity and is highly comfortable to wear. The knitted fabric is formed by hole-shaped coils and is highly breathable. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The present invention is a flow chart of the preparation process of the moisture-permeable and sun-proof layered composite fabric;

[0037] Figure 2 It is a bar graph showing the test results of the moisture permeability performance of the moisture permeable sunscreen layered composite fabrics prepared in Examples 1-5 of the present invention and Comparative Examples 1-2;

[0038] Figure 3 A bar graph showing the sunscreen performance test results of the moisture-permeable and sunscreen layered composite fabrics prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention;

[0039] Figure 4 It is a bar graph showing the test results of tensile properties of polylactic acid fiber filaments prepared in Examples 1-5 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0040] Example 1

[0041] This embodiment discloses a method for preparing a moisture-permeable sun-proof layered composite fabric, comprising the following steps:

[0042] Step 1, adding nitrile rubber, olefin-modified nano zinc oxide, and 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran, wherein the mass ratio of nitrile rubber, olefin-modified nano zinc oxide, 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran is 60:15:55:500, and ultrasonically mixing at a frequency of 50 kHz for 30 minutes to obtain a monomer dispersion;

[0043] Add dibenzoyl peroxide to chloroform, the mass ratio of dibenzoyl peroxide to chloroform is 1:25, and stir at a stirring speed of 150 r / min until dissolved to obtain an initiator solution;

[0044] Adding polylactic acid to tetrahydrofuran, with a mass ratio of polylactic acid to tetrahydrofuran being 100:550, stirring at a temperature of 60° C. and a stirring speed of 150 r / min until dissolved, to obtain a polylactic acid solution;

[0045] A monomer dispersion and an initiator solution are added dropwise to a polylactic acid solution, wherein the mass ratio of the polylactic acid solution, the monomer dispersion and the initiator solution is 650:630:52, and the dropping time of the monomer dispersion and the initiator solution is the same, which is 60 min. After the dropping is completed, the mixture is refluxed at 60° C. for 7 h. After the reaction is completed, a reaction mixture is obtained, and deionized water 3 times the mass of the reaction mixture is added to the reaction mixture to precipitate the reaction product, and the precipitate is filtered out, and the precipitate is washed 3 times with deionized water, and then washed 3 times with ethanol, and placed in a 50° C. drying oven for 15 h to obtain a modified polylactic acid;

[0046] Wherein, the olefin-modified nano zinc oxide is prepared by the following steps:

[0047] Add nano zinc oxide to a 95wt% ethanol aqueous solution, mix ultrasonically at a frequency of 50kHz for 30 minutes, add a 1mol / L hydrochloric acid aqueous solution to adjust the pH value to 3 to obtain a nano zinc oxide dispersion, add γ-methacryloxypropyltrimethoxysilane to the nano zinc oxide dispersion, the mass ratio of nano zinc oxide, γ-methacryloxypropyltrimethoxysilane and 95wt% ethanol aqueous solution is 8:10:100, react at a temperature of 55°C for 10 hours, filter after the reaction, wash the filtered residue with deionized water for 3 times, and dry it in a drying oven at 50°C for 12 hours to obtain olefin-modified nano zinc oxide;

[0048] Step 2, melt spinning the modified polylactic acid to obtain polylactic acid fiber filaments, wherein the single fiber fineness of the polylactic acid fiber filaments is 1.5D;

[0049] The melt spinning process includes: spinning temperature of 220°C; winding speed of 350m / min; drawing temperature of 135°C, drawing ratio of 5 times; heat setting temperature of 110°C;

[0050] The polylactic acid fiber filament is spun into fabric through a knitting process to obtain a polylactic acid fabric, and the weight of the polylactic acid fabric is 100g / m 2 ;

[0051] Step 3: Blend hemp fiber and cotton fiber, the mass ratio of hemp fiber to cotton fiber is 50:50, to obtain blended yarn, the yarn count of the blended yarn is 40S, the blended yarn is spun into fabric through knitting process, to obtain hemp / cotton blended fabric, the gram weight of hemp / cotton blended fabric is 100g / m 2 ;

[0052] The blending process includes: opening hemp fiber and cotton fiber separately, mixing them, and then processing them through mixed opening, carding, drawing, roving and spinning in sequence;

[0053] Among them, when the modified spandex fiber and hemp fiber are opened and mixed, the opening process adopts a rotation speed 5% lower than that of the conventional cotton fiber. The process of the combing process is to use a wool-type roller carding machine to comb the mixed fiber, and the rotation speed of the large cylinder of the wool-type roller carding machine is 90r / min. The process of the drawing process is to adopt a three-pass drawing process, each of which uses 8 feedings, and the back zone drafting multiple of the first drawing is 1.6 times, and the back zone drafting multiples of the second and third drawing are the same, both 1.1 times. The process parameters of the roving process are: the roving Tex twist coefficient is 50, the spindle speed is 480r / min, and the process parameters of the spun yarn process are: the spun yarn Tex twist coefficient is 340, the spun yarn speed is 12m / min, and the spindle speed is 5000r / min;

[0054] Hemp / cotton blended fabric is used as the inner fabric, polylactic acid fabric is used as the outer fabric, and pure cotton sewing thread is used to compound the inner fabric and the outer fabric with equal areas to prepare a moisture-permeable and sun-proof layered composite fabric.

[0055] Example 2

[0056] This embodiment discloses a method for preparing a moisture-permeable sun-proof layered composite fabric, comprising the following steps:

[0057] Step 1, adding nitrile rubber, olefin-modified nano zinc oxide, and 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran, wherein the mass ratio of nitrile rubber, olefin-modified nano zinc oxide, 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran is 80:20:70:700, and ultrasonically mixing at a frequency of 50 kHz for 30 minutes to obtain a monomer dispersion;

[0058] Add dibenzoyl peroxide to chloroform, the mass ratio of dibenzoyl peroxide to chloroform is 1:35, and stir at a stirring speed of 150 r / min until dissolved to obtain an initiator solution;

[0059] Adding polylactic acid to tetrahydrofuran, with a mass ratio of polylactic acid to tetrahydrofuran being 100:750, stirring at a temperature of 60° C. and a stirring speed of 150 r / min until dissolved, to obtain a polylactic acid solution;

[0060] A monomer dispersion and an initiator solution are added dropwise to a polylactic acid solution, wherein the mass ratio of the polylactic acid solution, the monomer dispersion and the initiator solution is 850:870:72, and the dropping time of the monomer dispersion and the initiator solution is the same, which is 90 min. After the dropping is completed, the mixture is refluxed at 70° C. for 5 h. After the reaction is completed, a reaction mixture is obtained, and deionized water 3 times the mass of the reaction mixture is added to the reaction mixture to precipitate the reaction product, and the precipitate is filtered out, and the precipitate is washed 3 times with deionized water, and then washed 3 times with ethanol, and placed in a 50° C. drying oven for 15 h to obtain a modified polylactic acid;

[0061] Wherein, the olefin-modified nano zinc oxide is prepared by the following steps:

[0062] Add nano zinc oxide to a 95 wt % ethanol aqueous solution, mix ultrasonically at a frequency of 50 kHz for 30 min, add a 1 mol / L hydrochloric acid aqueous solution to adjust the pH value to 4 to obtain a nano zinc oxide dispersion, add γ-methacryloxypropyltrimethoxysilane to the nano zinc oxide dispersion, the mass ratio of nano zinc oxide, γ-methacryloxypropyltrimethoxysilane and 95 wt % ethanol aqueous solution is 8:15:120, react at 65° C. for 8 h, filter after the reaction, wash the filtered residue with deionized water 3 times, and dry it in a 50° C. drying oven for 12 h to obtain olefin-modified nano zinc oxide;

[0063] Step 2, melt spinning the modified polylactic acid to obtain polylactic acid fiber filaments, wherein the single fiber fineness of the polylactic acid fiber filaments is 1.5D;

[0064] The melt spinning process includes: spinning temperature of 230°C; winding speed of 450m / min; drawing temperature of 145°C, drawing ratio of 5 times; heat setting temperature of 120°C;

[0065] The polylactic acid fiber filament is spun into fabric through a knitting process to obtain a polylactic acid fabric, the weight of which is 120g / m 2 ;

[0066] Step 3: Blend hemp fiber and cotton fiber, the mass ratio of hemp fiber to cotton fiber is 60:40, to obtain blended yarn, the yarn count of the blended yarn is 50S, the blended yarn is spun into fabric through knitting process, to obtain hemp / cotton blended fabric, the gram weight of hemp / cotton blended fabric is 120g / m 2 ;

[0067] The blending process includes: opening hemp fiber and cotton fiber separately, mixing them, and then processing them through mixed opening, carding, drawing, roving and spinning in sequence;

[0068] Among them, when the modified spandex fiber and hemp fiber are opened and mixed, the opening process adopts a rotation speed 10% lower than that of the conventional cotton fiber. The process of the carding process is to use a wool-type roller carding machine to card the mixed fiber, and the rotation speed of the large cylinder of the wool-type roller carding machine is 100r / min. The process of the drawing process is to adopt a three-pass drawing process, each of which uses 8 feedings, and the back zone drafting multiple of the first drawing is 1.8 times, and the back zone drafting multiples of the second and third drawing are the same, both 1.05 times. The process parameters of the roving process are: the roving Tex twist coefficient is 55, the spindle speed is 460r / min, and the process parameters of the spun yarn process are: the spun yarn Tex twist coefficient is 360, the spun yarn speed is 16m / min, and the spindle speed is 7000r / min;

[0069] Hemp / cotton blended fabric is used as the inner fabric, polylactic acid fabric is used as the outer fabric, and pure cotton sewing thread is used to compound the inner fabric and the outer fabric with equal areas to prepare a moisture-permeable and sun-proof layered composite fabric.

[0070] Example 3

[0071] This embodiment discloses a method for preparing a moisture-permeable sun-proof layered composite fabric, comprising the following steps:

[0072] Step 1, adding nitrile rubber, olefin-modified nano zinc oxide, and 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran, wherein the mass ratio of nitrile rubber, olefin-modified nano zinc oxide, 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran is 65:16:58:550, and ultrasonically mixing at a frequency of 50 kHz for 30 minutes to obtain a monomer dispersion;

[0073] Add dibenzoyl peroxide to chloroform, the mass ratio of dibenzoyl peroxide to chloroform is 1:30, and stir at a stirring speed of 150 r / min until dissolved to obtain an initiator solution;

[0074] Adding polylactic acid to tetrahydrofuran in a mass ratio of polylactic acid to tetrahydrofuran of 100:600, stirring at a temperature of 60° C. and a stirring speed of 150 r / min until dissolved, to obtain a polylactic acid solution;

[0075] A monomer dispersion and an initiator solution are added dropwise to a polylactic acid solution, wherein the mass ratio of the polylactic acid solution, the monomer dispersion and the initiator solution is 700:680:58, and the dropping time of the monomer dispersion and the initiator solution is the same, which is 70 min. After the dropping is completed, the mixture is refluxed at 65° C. for 6 h. After the reaction is completed, a reaction mixture is obtained, and deionized water 3 times the mass of the reaction mixture is added to the reaction mixture to precipitate the reaction product, and the precipitate is filtered out, and the precipitate is washed 3 times with deionized water, and then washed 3 times with ethanol, and placed in a 50° C. drying oven for 15 h to obtain a modified polylactic acid;

[0076] Wherein, the olefin-modified nano zinc oxide is prepared by the following steps:

[0077] Add nano zinc oxide to a 95wt% ethanol aqueous solution, mix ultrasonically at a frequency of 50kHz for 30min, add a 1mol / L hydrochloric acid aqueous solution to adjust the pH value to 3.5 to obtain a nano zinc oxide dispersion, add γ-methacryloxypropyltrimethoxysilane to the nano zinc oxide dispersion, the mass ratio of nano zinc oxide, γ-methacryloxypropyltrimethoxysilane and 95wt% ethanol aqueous solution is 8:11:105, react at 60°C for 9h, filter after the reaction, wash the filtered residue with deionized water 3 times, and dry it in a 50°C drying oven for 12h to obtain olefin-modified nano zinc oxide;

[0078] Step 2, melt spinning the modified polylactic acid to obtain polylactic acid fiber filaments, wherein the single fiber fineness of the polylactic acid fiber filaments is 1.5D;

[0079] The melt spinning process includes: spinning temperature of 225°C; winding speed of 400m / min; drawing temperature of 140°C, drawing ratio of 5 times; heat setting temperature of 115°C;

[0080] The polylactic acid fiber filament is spun into fabric through a knitting process to obtain a polylactic acid fabric, the weight of which is 110g / m 2 ;

[0081] Step 3: Blend hemp fiber and cotton fiber, the mass ratio of hemp fiber to cotton fiber is 55:45, to obtain blended yarn, the yarn count of the blended yarn is 45S, the blended yarn is spun into fabric through knitting process, to obtain hemp / cotton blended fabric, the gram weight of hemp / cotton blended fabric is 110g / m 2 ;

[0082] The blending process includes: opening hemp fiber and cotton fiber separately, mixing them, and then processing them through mixed opening, carding, drawing, roving and spinning in sequence;

[0083] Among them, when the modified spandex fiber and hemp fiber are opened and mixed, the opening process adopts a rotation speed 7% lower than that of the conventional cotton fiber. The process of the combing process is to use a wool-type roller carding machine to comb the mixed fiber. The rotation speed of the large cylinder of the wool-type roller carding machine is 95r / min. The process of the drawing process is to adopt a three-pass drawing process, each of which uses 8 feedings. The back zone drafting multiple of the first drawing is 1.7 times, and the back zone drafting multiples of the second and third drawing are the same, both 1.08 times. The process parameters of the roving process are: the roving Tex twist coefficient is 55, the spindle speed is 470r / min, and the process parameters of the spun yarn process are: the spun yarn Tex twist coefficient is 350, the spun yarn speed is 14m / min, and the spindle speed is 6000r / min.

[0084] Hemp / cotton blended fabric is used as the inner fabric, polylactic acid fabric is used as the outer fabric, and pure cotton sewing thread is used to compound the inner fabric and the outer fabric with equal areas to prepare a moisture-permeable and sun-proof layered composite fabric.

[0085] Example 4

[0086] This embodiment discloses a method for preparing a moisture-permeable sun-proof layered composite fabric, comprising the following steps:

[0087] Step 1, adding nitrile rubber, olefin-modified nano zinc oxide, and 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran, wherein the mass ratio of nitrile rubber, olefin-modified nano zinc oxide, 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran is 70:17.5:62:600, and ultrasonically mixing at a frequency of 50 kHz for 30 minutes to obtain a monomer dispersion;

[0088] Add dibenzoyl peroxide to chloroform, the mass ratio of dibenzoyl peroxide to chloroform is 1:30, and stir at a stirring speed of 150 r / min until dissolved to obtain an initiator solution;

[0089] Adding polylactic acid to tetrahydrofuran, with a mass ratio of polylactic acid to tetrahydrofuran being 100:650, stirring at a temperature of 60° C. and a stirring speed of 150 r / min until dissolved, to obtain a polylactic acid solution;

[0090] A monomer dispersion and an initiator solution are added dropwise to a polylactic acid solution, wherein the mass ratio of the polylactic acid solution, the monomer dispersion and the initiator solution is 750:750:64, and the dropping time of the monomer dispersion and the initiator solution is the same, which is 75 min. After the dropping is completed, the mixture is refluxed at 65° C. for 6 h. After the reaction is completed, a reaction mixture is obtained, and deionized water 3 times the mass of the reaction mixture is added to the reaction mixture to precipitate the reaction product, and the precipitate is filtered out, and the precipitate is washed 3 times with deionized water, and then washed 3 times with ethanol, and dried in a drying oven at 50° C. for 15 h to obtain a modified polylactic acid;

[0091] Wherein, the olefin-modified nano zinc oxide is prepared by the following steps:

[0092] Add nano zinc oxide to a 95wt% ethanol aqueous solution, mix ultrasonically at a frequency of 50kHz for 30min, add a 1mol / L hydrochloric acid aqueous solution to adjust the pH value to 3.5 to obtain a nano zinc oxide dispersion, add γ-methacryloxypropyltrimethoxysilane to the nano zinc oxide dispersion, the mass ratio of nano zinc oxide, γ-methacryloxypropyltrimethoxysilane and 95wt% ethanol aqueous solution is 8:12.5:110, react at 60°C for 9h, filter after the reaction, wash the filtered residue with deionized water for 3 times, and dry it in a 50°C drying oven for 12h to obtain olefin-modified nano zinc oxide;

[0093] Step 2, melt spinning the modified polylactic acid to obtain polylactic acid fiber filaments, wherein the single fiber fineness of the polylactic acid fiber filaments is 1.5D;

[0094] The melt spinning process includes: spinning temperature of 225°C; winding speed of 400m / min; drawing temperature of 140°C, drawing ratio of 5 times; heat setting temperature of 115°C;

[0095] The polylactic acid fiber filament is spun into fabric through a knitting process to obtain a polylactic acid fabric, the weight of which is 110g / m 2 ;

[0096] Step 3: Blend hemp fiber and cotton fiber, the mass ratio of hemp fiber to cotton fiber is 55:45, to obtain blended yarn, the yarn count of the blended yarn is 45S, the blended yarn is spun into fabric through knitting process, to obtain hemp / cotton blended fabric, the gram weight of hemp / cotton blended fabric is 110g / m 2 ;

[0097] The blending process includes: opening hemp fiber and cotton fiber separately, mixing them, and then processing them through mixed opening, carding, drawing, roving and spinning in sequence;

[0098] Among them, when the modified spandex fiber and hemp fiber are opened and mixed, the opening process adopts a rotation speed 7.5% lower than that of the conventional cotton fiber. The process of the carding process is to use a wool-type roller carding machine to card the mixed fiber. The rotation speed of the large cylinder of the wool-type roller carding machine is 95r / min. The process of the drawing process is to adopt a three-pass drawing process, each of which uses 8 feedings. The back zone drafting multiple of the first drawing is 1.7 times, and the back zone drafting multiples of the second and third drawing are the same, both 1.08 times. The process parameters of the roving process are: the roving Tex twist coefficient is 55, the spindle speed is 470r / min, and the process parameters of the spun yarn process are: the spun yarn Tex twist coefficient is 350, the spun yarn speed is 14m / min, and the spindle speed is 6000r / min.

[0099] Hemp / cotton blended fabric is used as the inner fabric, polylactic acid fabric is used as the outer fabric, and pure cotton sewing thread is used to compound the inner fabric and the outer fabric with equal areas to prepare a moisture-permeable and sun-proof layered composite fabric.

[0100] Example 5

[0101] This embodiment discloses a method for preparing a moisture-permeable sun-proof layered composite fabric, comprising the following steps:

[0102] Step 1, adding nitrile rubber, olefin-modified nano zinc oxide, and 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran, wherein the mass ratio of nitrile rubber, olefin-modified nano zinc oxide, 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran is 75:19:66:650, and ultrasonically mixing at a frequency of 50 kHz for 30 minutes to obtain a monomer dispersion;

[0103] Add dibenzoyl peroxide to chloroform, the mass ratio of dibenzoyl peroxide to chloroform is 1:30, and stir at a stirring speed of 150 r / min until dissolved to obtain an initiator solution;

[0104] Adding polylactic acid to tetrahydrofuran, with a mass ratio of polylactic acid to tetrahydrofuran being 100:700, stirring at a temperature of 60° C. and a stirring speed of 150 r / min until dissolved, to obtain a polylactic acid solution;

[0105] A monomer dispersion and an initiator solution are added dropwise to a polylactic acid solution, wherein the mass ratio of the polylactic acid solution, the monomer dispersion and the initiator solution is 850:810:68, and the dropping time of the monomer dispersion and the initiator solution is the same, which is 80 min. After the dropping is completed, the mixture is refluxed at 65° C. for 6 h. After the reaction is completed, a reaction mixture is obtained, and deionized water 3 times the mass of the reaction mixture is added to the reaction mixture to precipitate the reaction product, and the precipitate is filtered out, and the precipitate is washed 3 times with deionized water, and then washed 3 times with ethanol, and placed in a 50° C. drying oven for 15 h to obtain a modified polylactic acid;

[0106] Wherein, the olefin-modified nano zinc oxide is prepared by the following steps:

[0107] Add nano zinc oxide to a 95 wt % ethanol aqueous solution, mix ultrasonically at a frequency of 50 kHz for 30 min, add a 1 mol / L hydrochloric acid aqueous solution to adjust the pH value to 3.5 to obtain a nano zinc oxide dispersion, add γ-methacryloxypropyltrimethoxysilane to the nano zinc oxide dispersion, the mass ratio of nano zinc oxide, γ-methacryloxypropyltrimethoxysilane and 95 wt % ethanol aqueous solution is 8:14:115, react at 60° C. for 9 h, filter after the reaction, wash the filtered residue with deionized water 3 times, and dry it in a 50° C. drying oven for 12 h to obtain olefin-modified nano zinc oxide;

[0108] Step 2, melt spinning the modified polylactic acid to obtain polylactic acid fiber filaments, wherein the single fiber fineness of the polylactic acid fiber filaments is 1.5D;

[0109] The melt spinning process includes: spinning temperature of 225°C; winding speed of 400m / min; drawing temperature of 140°C, drawing ratio of 5 times; heat setting temperature of 115°C;

[0110] The polylactic acid fiber filament is spun into fabric through a knitting process to obtain a polylactic acid fabric, the weight of which is 110g / m 2 ;

[0111] Step 3: Blend hemp fiber and cotton fiber, the mass ratio of hemp fiber to cotton fiber is 55:45, to obtain blended yarn, the yarn count of the blended yarn is 45S, the blended yarn is spun into fabric through knitting process, to obtain hemp / cotton blended fabric, the gram weight of hemp / cotton blended fabric is 110g / m 2 ;

[0112] The blending process includes: opening hemp fiber and cotton fiber separately, mixing them, and then processing them through mixed opening, carding, drawing, roving and spinning in sequence;

[0113] Among them, when the modified spandex fiber and hemp fiber are opened and mixed, the opening process adopts a rotation speed 7.5% lower than that of the conventional cotton fiber. The process of the carding process is to use a wool-type roller carding machine to card the mixed fiber. The rotation speed of the large cylinder of the wool-type roller carding machine is 95r / min. The process of the drawing process is to adopt a three-pass drawing process, each of which uses 8 feedings. The back zone drafting multiple of the first drawing is 1.7 times, and the back zone drafting multiples of the second and third drawing are the same, both 1.08 times. The process parameters of the roving process are: the roving Tex twist coefficient is 55, the spindle speed is 470r / min, and the process parameters of the spun yarn process are: the spun yarn Tex twist coefficient is 350, the spun yarn speed is 14m / min, and the spindle speed is 6000r / min.

[0114] Hemp / cotton blended fabric is used as the inner fabric, polylactic acid fabric is used as the outer fabric, and pure cotton sewing thread is used to compound the inner fabric and the outer fabric with equal areas to prepare a moisture-permeable and sun-proof layered composite fabric.

[0115] Comparative Example 1

[0116] This comparative example discloses a method for preparing a moisture-permeable sun-proof layered composite fabric, comprising the following steps:

[0117] Step 1, adding nitrile rubber, nano zinc oxide, and 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran, wherein the mass ratio of nitrile rubber, nano zinc oxide, 2-hydroxy-4-(methacryloyloxy) benzophenone to tetrahydrofuran is 80:20:70:700, and ultrasonically mixing at a frequency of 50 kHz for 30 minutes to obtain a monomer dispersion;

[0118] Add dibenzoyl peroxide to chloroform, the mass ratio of dibenzoyl peroxide to chloroform is 1:35, and stir at a stirring speed of 150 r / min until dissolved to obtain an initiator solution;

[0119] Adding polylactic acid to tetrahydrofuran, with a mass ratio of polylactic acid to tetrahydrofuran being 100:750, stirring at a temperature of 60° C. and a stirring speed of 150 r / min until dissolved, to obtain a polylactic acid solution;

[0120] A monomer dispersion and an initiator solution are added dropwise to a polylactic acid solution, wherein the mass ratio of the polylactic acid solution, the monomer dispersion and the initiator solution is 850:870:72, and the dropping time of the monomer dispersion and the initiator solution is the same, which is 90 min. After the dropping is completed, the mixture is refluxed at 70° C. for 5 h. After the reaction is completed, a reaction mixture is obtained, and deionized water 3 times the mass of the reaction mixture is added to the reaction mixture to precipitate the reaction product, and the precipitate is filtered out, and the precipitate is washed 3 times with deionized water, and then washed 3 times with ethanol, and placed in a 50° C. drying oven for 15 h to obtain a modified polylactic acid;

[0121] Step 2, melt spinning the modified polylactic acid to obtain polylactic acid fiber filaments, wherein the single fiber fineness of the polylactic acid fiber filaments is 1.5D;

[0122] The melt spinning process includes: spinning temperature of 230°C; winding speed of 450m / min; drawing temperature of 145°C, drawing ratio of 5 times; heat setting temperature of 120°C;

[0123] The polylactic acid fiber filament is spun into fabric through a knitting process to obtain a polylactic acid fabric, the weight of which is 120g / m 2 ;

[0124] Step 3: Blend hemp fiber and cotton fiber, the mass ratio of hemp fiber to cotton fiber is 60:40, to obtain blended yarn, the yarn count of the blended yarn is 50S, the blended yarn is spun into fabric through knitting process, to obtain hemp / cotton blended fabric, the gram weight of hemp / cotton blended fabric is 120g / m 2 ;

[0125] The blending process includes: opening hemp fiber and cotton fiber separately, mixing them, and then processing them through mixed opening, carding, drawing, roving and spinning in sequence;

[0126] Among them, when the modified spandex fiber and hemp fiber are opened and mixed, the opening process adopts a rotation speed 10% lower than that of the conventional cotton fiber. The process of the carding process is to use a wool-type roller carding machine to card the mixed fiber, and the rotation speed of the large cylinder of the wool-type roller carding machine is 100r / min. The process of the drawing process is to adopt a three-pass drawing process, each of which uses 8 feedings, and the back zone drafting multiple of the first drawing is 1.8 times, and the back zone drafting multiples of the second and third drawing are the same, both 1.05 times. The process parameters of the roving process are: the roving Tex twist coefficient is 55, the spindle speed is 460r / min, and the process parameters of the spun yarn process are: the spun yarn Tex twist coefficient is 360, the spun yarn speed is 16m / min, and the spindle speed is 7000r / min;

[0127] Hemp / cotton blended fabric is used as the inner fabric, polylactic acid fabric is used as the outer fabric, and pure cotton sewing thread is used to compound the inner fabric and the outer fabric with equal areas to prepare a moisture-permeable and sun-proof layered composite fabric.

[0128] Comparative Example 2

[0129] This comparative example discloses a method for preparing a moisture-permeable sun-proof layered composite fabric, comprising the following steps:

[0130] Step 1, adding nitrile rubber and 2-hydroxy-4-(methacryloyloxy)benzophenone to tetrahydrofuran, wherein the mass ratio of nitrile rubber, 2-hydroxy-4-(methacryloyloxy)benzophenone to tetrahydrofuran is 80:0:720, and ultrasonically mixing at a frequency of 50 kHz for 30 minutes to obtain a monomer dispersion;

[0131] Add dibenzoyl peroxide to chloroform, the mass ratio of dibenzoyl peroxide to chloroform is 1:35, and stir at a stirring speed of 150 r / min until dissolved to obtain an initiator solution;

[0132] Adding polylactic acid to tetrahydrofuran, with a mass ratio of polylactic acid to tetrahydrofuran being 100:750, stirring at a temperature of 60° C. and a stirring speed of 150 r / min until dissolved, to obtain a polylactic acid solution;

[0133] A monomer dispersion and an initiator solution are added dropwise to a polylactic acid solution, wherein the mass ratio of the polylactic acid solution, the monomer dispersion and the initiator solution is 850:870:72, and the dropping time of the monomer dispersion and the initiator solution is the same, which is 90 min. After the dropping is completed, the mixture is refluxed at 70° C. for 5 h. After the reaction is completed, a reaction mixture is obtained, and deionized water 3 times the mass of the reaction mixture is added to the reaction mixture to precipitate the reaction product, and the precipitate is filtered out, and the precipitate is washed 3 times with deionized water, and then washed 3 times with ethanol, and placed in a 50° C. drying oven for 15 h to obtain a modified polylactic acid;

[0134] Step 2, melt spinning the modified polylactic acid to obtain polylactic acid fiber filaments, wherein the single fiber fineness of the polylactic acid fiber filaments is 1.5D;

[0135] The melt spinning process includes: spinning temperature of 230°C; winding speed of 450m / min; drawing temperature of 145°C, drawing ratio of 5 times; heat setting temperature of 120°C;

[0136] The polylactic acid fiber filament is spun into fabric through a knitting process to obtain a polylactic acid fabric, the weight of which is 120g / m 2 ;

[0137] Step 3: Blend hemp fiber and cotton fiber, the mass ratio of hemp fiber to cotton fiber is 60:40, to obtain blended yarn, the yarn count of the blended yarn is 50S, the blended yarn is spun into fabric through knitting process, to obtain hemp / cotton blended fabric, the gram weight of hemp / cotton blended fabric is 120g / m 2 ;

[0138] The blending process includes: opening hemp fiber and cotton fiber separately, mixing them, and then processing them through mixed opening, carding, drawing, roving and spinning in sequence;

[0139] Among them, when the modified spandex fiber and hemp fiber are opened and mixed, the opening process adopts a rotation speed 10% lower than that of the conventional cotton fiber. The process of the carding process is to use a wool-type roller carding machine to card the mixed fiber, and the rotation speed of the large cylinder of the wool-type roller carding machine is 100r / min. The process of the drawing process is to adopt a three-pass drawing process, each of which uses 8 feedings, and the back zone drafting multiple of the first drawing is 1.8 times, and the back zone drafting multiples of the second and third drawing are the same, both 1.05 times. The process parameters of the roving process are: the roving Tex twist coefficient is 55, the spindle speed is 460r / min, and the process parameters of the spun yarn process are: the spun yarn Tex twist coefficient is 360, the spun yarn speed is 16m / min, and the spindle speed is 7000r / min;

[0140] Hemp / cotton blended fabric is used as the inner fabric, polylactic acid fabric is used as the outer fabric, and pure cotton sewing thread is used to compound the inner fabric and the outer fabric with equal areas to prepare a moisture-permeable and sun-proof layered composite fabric.

[0141] In the above embodiments and comparative examples, the nitrile rubber is liquid nitrile rubber purchased from Dongguan Chengjie Plastic Raw Materials Co., Ltd., model: RB302, molecular weight: 10,000-20,000; polylactic acid is purchased from Anhui Fengyuan Futailai Polylactic Acid Co., Ltd., brand: FY601, density: 1.24 g / m 3 , melting point: 170℃, melt index (190℃ / 2.16kg): 9; nano zinc oxide was purchased from Shijiazhuang Guanchi Chemical Technology Co., Ltd., particle size: 30-50nm; hemp fiber was purchased from Jingde County Jinwei Hemp Industry Co., Ltd., fiber strength ≥235, fiber length ≥130mm, and was chopped before use to make the length between 35-40mm; cotton fiber was long-staple cotton produced in Xinjiang with a length of 38-39.7mm; all-cotton sewing thread was purchased from Taizhou Yidu Clothing Co., Ltd., product specification: 40S / 2.

[0142] Test example

[0143] The performance tests were conducted on the moisture-permeable and sun-proof layered composite fabrics prepared in the above embodiments and comparative examples:

[0144] (1) Moisture permeability test: The moisture permeability of the inner fabrics prepared in Examples 1-5 and Comparative Examples 1-2 was measured with reference to the standard GB / T12704.1-2009 "Textile fabric moisture permeability test method Part 1: Moisture absorption method", and the results are shown in Table 1:

[0145] Table 1

[0146]

[0147] As can be seen from Table 1, the moisture-permeable sunscreen layered composite fabric prepared by the present invention has good moisture permeability. Both hemp fiber and cotton fiber have excellent moisture absorption performance, and the cross section of the hemp fiber presents a hollow structure, with many cracks and holes connected to it in the longitudinal direction, so that the hemp fiber has more capillaries, which can quickly diffuse and transfer water and achieve good moisture permeability. The preparation process of the inner layer fabric in Comparative Examples 1 and 2 is the same as that in Example 2, and the moisture permeability is similar.

[0148] (2) Sunscreen performance test: The UPF (ultraviolet protection factor) of the outer fabrics prepared in Examples 1-5 and Comparative Examples 1-2 was measured with reference to the standard GB / T18830-2009 "Evaluation of UV protection performance of textiles". The results are shown in Table 2:

[0149] Table 2

[0150]

[0151] As shown in Table 2, the moisture-permeable sunscreen layered composite fabric prepared by the present invention has good sunscreen performance. In the modification process of polylactic acid, the introduction of sunscreen components nano zinc oxide and 2-hydroxy-4-(methacryloyloxy) benzophenone can effectively improve the sunscreen performance. Under the action of the initiator, the alkenyl-modified nano zinc oxide and 2-hydroxy-4-(methacryloyloxy) benzophenone are grafted copolymerized on the polylactic acid molecular chain through the carbon-carbon double bonds contained in their respective molecules, and the sunscreen components are connected to the polylactic acid molecules in a chemically bonded manner, avoiding the phenomenon of reduced toughening sunscreen effect caused by the poor dispersion compatibility of inorganic sunscreen components and polylactic acid and the migration of organic sunscreen components. Compared with Example 2, in Comparative Example 1, the inorganic sunscreen component is nano zinc oxide, which is not connected to the polylactic acid molecule through an alkenyl group, and the dispersion compatibility in the polylactic acid is reduced, and the sunscreen performance is reduced; in Comparative Example 2, no inorganic sunscreen component is added, and the sunscreen performance is further reduced.

[0152] (3) Tensile performance test: The tensile properties of the polylactic acid fiber filaments prepared in Examples 1-5 and Comparative Examples 1-2 were measured with reference to the standard GB / T14344-2022 "Tensile test method for chemical fiber filaments". The results are shown in Table 3:

[0153] Table 3

[0154]

[0155] As shown in Table 3, the moisture-permeable sun-proof layered composite fabric prepared by the present invention has good tensile properties. The introduction of the toughening component nitrile rubber can effectively improve the elongation at break of the polylactic acid fiber filaments, and at the same time, the addition of nano zinc oxide can improve the breaking strength of the polylactic acid fiber filaments. Compared with Example 2, in Comparative Example 1, nano zinc oxide is not connected to the polylactic acid molecule through an olefin group, and the dispersion compatibility in polylactic acid is reduced, which has no obvious effect on the elongation at break, but the breaking strength is reduced; in Comparative Example 2, nano zinc oxide is not added, and the breaking strength is further reduced.

[0156] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a moisture-permeable and sun-proof layered composite fabric, characterized in that: The steps include: Step 1: adding nitrile rubber, olefin-modified nano zinc oxide and 2-hydroxy-4-(methacryloyloxy)benzophenone into tetrahydrofuran, and mixing by ultrasonication to obtain a monomer dispersion; Add dibenzoyl peroxide into chloroform, stir and dissolve to obtain an initiator solution; Adding polylactic acid into tetrahydrofuran to dissolve it to obtain a polylactic acid solution, dropping a monomer dispersion and an initiator solution into the polylactic acid solution, reacting after the dropping is complete, settling after the reaction is complete, filtering, washing, and drying to obtain a modified polylactic acid; Step 2, melt spinning the modified polylactic acid to obtain polylactic acid fiber filaments; The polylactic acid fiber filaments are spun into fabrics through a knitting process to obtain polylactic acid fabrics; Step 3: blending hemp fiber and cotton fiber to obtain blended yarn, and spinning the blended yarn into fabric through a knitting process to obtain hemp / cotton blended fabric; The hemp / cotton blended fabric is used as the inner fabric and the polylactic acid fabric is used as the outer fabric. The inner fabric and the outer fabric are laminated with equal areas to prepare a moisture-permeable and sun-proof layered composite fabric.

2. The method for preparing a moisture-permeable sun-proof layered composite fabric according to claim 1, characterized in that: In the step 1, the mass ratio of the polylactic acid solution, the monomer dispersion and the initiator solution is (650-850):(630-870):(52-72); the dropping time of the monomer dispersion and the initiator solution is the same, both of which are 60-90 minutes; the reaction conditions are reflux reaction at a temperature of 60-70° C. for 5-7 hours.

3. The method for preparing a moisture-permeable sun-proof layered composite fabric according to claim 1, characterized in that: In the step 1, in the monomer dispersion, the mass ratio of nitrile rubber, olefin-modified nano zinc oxide, 2-hydroxy-4-(methacryloyloxy) benzophenone, and tetrahydrofuran is (60-80):(15-20):(55-70):(500-700); in the initiator solution, the mass ratio of dibenzoyl peroxide to chloroform is 1:(25-35); in the polylactic acid solution, the mass ratio of polylactic acid to tetrahydrofuran is 100:(550-750).

4. The method for preparing a moisture-permeable sun-proof layered composite fabric according to claim 1, characterized in that: The alkenyl-modified nano zinc oxide in step 1 is prepared by the following steps: The nano zinc oxide is added into an ethanol aqueous solution, and after ultrasonic dispersion, the pH value is adjusted to 3-4 to obtain a nano zinc oxide dispersion liquid. γ-methacryloxypropyltrimethoxysilane is added into the nano zinc oxide dispersion liquid to react. After the reaction is completed, the mixture is filtered, washed, and dried to obtain olefin-modified nano zinc oxide.

5. The method for preparing a moisture-permeable sun-proof layered composite fabric according to claim 4, characterized in that: The mass ratio of the nano zinc oxide, γ-methacryloxypropyltrimethoxysilane and ethanol aqueous solution is 8:(10-15):(100-120), and the reaction conditions are 55-65° C. for 8-10 hours.

6. The method for preparing a moisture-permeable sun-proof layered composite fabric according to claim 1, characterized in that: In the step 2: the melt spinning process includes: a spinning temperature of 220-230°C; a winding speed of 350-450m / min; a drawing temperature of 135-145°C, a drawing ratio of 5 times; and a heat setting temperature of 110-120°C.

7. The method for preparing a moisture-permeable sun-proof layered composite fabric according to claim 1, characterized in that: In the step 2, the fineness of the polylactic acid fiber filament is 1.4-1.6D, and the weight of the polylactic acid fabric is 100-120g / m 2 .

8. The method for preparing a moisture-permeable sun-proof layered composite fabric according to claim 1, characterized in that: In step 3, the mass ratio of hemp fiber to cotton fiber is (50-60):(40-50), the yarn count of the blended yarn is 40-50S, and the gram weight of the hemp / cotton blended fabric is 100-120g / m 2 ; The blending process includes: opening the hemp fiber and the cotton fiber separately, mixing them, and then processing them through the steps of mixed opening, carding, drawing, roving and spun spinning in sequence.

9. The method for preparing a moisture-permeable sun-proof layered composite fabric according to claim 8, characterized in that: When the modified spandex fiber and the hemp fiber are opened separately or mixed and opened, the opening process adopts a rotation speed 5-10% lower than that of the conventional cotton fiber opening. The process of the combing step is to use a wool-type roller-type combing machine to comb the mixed fiber, and the rotation speed of the large cylinder of the wool-type roller-type combing machine is 90-100r / min; The process of the drawing process is to adopt a three-pass drawing process, each of which adopts 8 feedings, the back zone drafting multiple of the first pass drawing is 1.6-1.8 times, and the back zone drafting multiples of the second and third passes drawing are the same, both of which are 1.05-1.1 times; The process parameters of the roving process are: the roving Tex twist coefficient is 50-55, and the spindle speed is 460-480r / min; The process parameters of the spinning process are: the spinning Tex twist coefficient is 340-360, the sliver delivery speed is 12-16m / min, and the spindle speed is 5000-7000r / min.

10. A moisture-permeable sun-proof layered composite fabric prepared by the method for preparing a moisture-permeable sun-proof layered composite fabric according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Cool and breathable fabric for sun-proof clothing and preparation method thereof

    CN117382267B

  • Super-soft non-woven fabric and preparation method thereof

    CN111876899A

  • Quick-dry sunscreen fabric based on hollow heat insulation fibers and preparation method of quick-dry sunscreen fabric

    CN118186745A

  • Moisture absorption and sweat releasing yarn based on China hemp fibers, preparation method and textile

    CN118957827A

  • Polylactic acid type stretched film, stretched laminated film and its use

    JP2007270076A